Bahan Ajar Menulis Naskah Drama Bermuatan Nilai Toleransi untuk Siswa Kelas VIII SMP/MTS - Isnaini Indra Nur Hayati; Nurhadi Nurhadi; Azizatuz Zahro (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This developmental research of teaching materials for writing drama scripts which contain tolerance values was constructed based on the students’ need in writing drama scripts. The purpose of this research is to apply the values of tolerance in their daily life in writing drama scripts. This research uses the method of Borg and Gall which is modified into seven stages. Expert tests were carried out on tolerance material experts, teaching media development experts, and practitioners. In the expert test, it was found that the presentation feasibility score was 85%, the graphic feasibility was 83%, the language feasibility was 83%, and the tolerance value aspect was 90%. Based on these results, it can be concluded that teaching materials for writing drama scripts which contain tolerance values are very feasible and can be implemented for the students.Abstrak: Penelitian pengembangan ini merupakan bahan ajar menulis drama bermuatan nilai toleransi ini dibuat berdasarkan kebutuhan siswa dalam menulis naskah drama. Tujuan dari penelitian ini adalah untuk menerapkan nilai-nilai toleransi dalam keseharian dalam naskah drama. Penelitian ini menggunakan metode dari Borg dan Gall yang dimodifikasi menjadi tujuh tahapan. Uji produk dilakukan oleh ahli materi toleransi, ahli pengembangan media bahan ajar, dan praktisi. Dalam uji ahli didapatkan skor kelayakan penyajian 85%, kelayakan kegrafikan 83%, kelayakan bahasa 83%, dan aspek nilai toleransi 90% Berdasarkan hasil tersebut, kesimpulannya adalah bahan ajar menulis naskah drama bermuatan nilai toleransi sangat layak dan dapat diimplementasikan.